2015
DOI: 10.1155/2015/867587
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and Pregnancy: A Review of the Literature from India

Abstract: Maternal influenza infection is known to cause substantial morbidity and mortality among pregnant women and young children. Many professional healthcare bodies including the World Health Organization (WHO) have identified pregnant women as a priority risk group for receipt of inactivated seasonal influenza vaccination. However influenza prevention in this group is not yet a public health priority in India. This literature review was undertaken to examine the Indian studies of influenza among pregnant women. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
1
36
1
Order By: Relevance
“…Fetal malformations and other illnesses have been noted in cases of influenza in pregnancy [8]. Preterm delivery is an oft-recognized adverse outcome, as has been studied by Newsome et al in the USA [3]. This study showed that 63.6 % of pregnant women severely ill with influenza had preterm deliveries and 43.8 % had low birth weight babies as compared to the national averages.…”
Section: Effects On Pregnancy Outcomesmentioning
confidence: 68%
See 4 more Smart Citations
“…Fetal malformations and other illnesses have been noted in cases of influenza in pregnancy [8]. Preterm delivery is an oft-recognized adverse outcome, as has been studied by Newsome et al in the USA [3]. This study showed that 63.6 % of pregnant women severely ill with influenza had preterm deliveries and 43.8 % had low birth weight babies as compared to the national averages.…”
Section: Effects On Pregnancy Outcomesmentioning
confidence: 68%
“…The immunity shifts away from the cell-mediated immunity toward the humoral immunity [2]. There is a selective suppression of the T helper-type I cell-mediated immunity, with resultant impaired maternal response to infection [3]. Put together with the organ system alterations, the pregnant woman is at an increased risk of severe influenza.…”
Section: Effects Of Influenza During Pregnancymentioning
confidence: 99%
See 3 more Smart Citations